3D printing of Ti3C2-MXene-incorporated composite scaffolds for accelerated bone regeneration. (1st May 2022) - Mi, Xue; Su, Zhenya; Fu, Yu; Li, Shiqi; Mo, Anchun
Abstract: Grafting of bone-substitute biomaterials plays a vital role in the reconstruction of bone defects. However, the design of bioscaffolds with osteoinductive agents and biomimetic structures for regeneration of critical-sized bone defects is difficult. Ti3 C2 MXene—belonging to a new class of 2D nanomaterials—exhibits excellent biocompatibility, and antibacterial properties, and promotes osteogenesis. However, its application in preparing 3D-printed tissue-engineered bone scaffolds for repairing bone defects has not been explored. In this work, Ti3 C2 MXene was incorporated into composite scaffolds composed of hydroxyapatite and sodium alginate via extrusion-based 3D printing to evaluate its potential in bone regeneration. MXene composite scaffolds were fabricated and characterized by SEM, XPS, mechanical properties and porosity. The biocompatibility and osteoinductivity of MXene composite scaffolds were evaluated by cell adhesion, cell counting kit-8 test, quantitative real-time polymerase chain reaction, alkaline phosphatase activity and alizarin red S tests of bone mesenchymal stem cells (BMSCs). A rat calvarial defect model was performed to explore the osteogenic activity of the MXene composite scaffolds in vivo . The results showed the obtained scaffold had a uniform structure, macropore morphology, and high mechanical strength. In vitro experimental results revealed that the scaffold exhibited excellent biocompatibility with BMSCs, promoted cell proliferation, upregulated osteogenic gene expression, enhanced alkaline phosphatase activity, and promoted mineralized-nodule formation. The experimental results confirmed that the scaffold effectively promoted bone regeneration in a model of critical-sized calvarial- bone-defect in vivo and promoted bone healing to a significantly greater degree than scaffolds without added Ti3 C2 MXene did. Conclusively, the Ti3 C2 MXene composite 3D-printed scaffolds are promising for clinical bone defect treatment, and the results of this study provide a theoretical basis for the development of practical applications for tissue-engineered bone scaffolds.